The Delivery of Stop Smoking Support to People with Mental Health Conditions: A Survey of NHS Stop Smoking Services - Ratschen Elena; McNally Lisa (BMC, 2010)
Abstract Background People with mental health problems exhibit smoking rates up to three times that of the general population. Metabolic interactions between hydrocarbon agents in tobacco smoke and some antipsychotic drugs account for a change in medication metabolism on stopping smoking, and potentially for increased blood levels. Nicotine withdrawal can mimic or exacerbate symptoms of mental illness. Therefore, appropriate screening for mental health problems and liaison with local mental health care providers should be a priority for NHS Stop Smoking Services. The present study aimed to examine this issue through surveys with NHS Stop Smoking Service staff in London. Methods Semi-structured telephone interviews were conducted with one senior staff member from 27 of the 29 NHS Stop Smoking Services in London. Results It was found that only a minority of services routinely check the mental health status or mental health service use of their clients. In addition, most services do not routinely implement special checks or actions when mental health problems are revealed. It was notable that respondents reported a lack of strategic drivers supporting work with mental health patients (such as targets relating to successful quits) as well as a low level of partnership working with local mental health care providers. Conclusions NHS Stop Smoking Services may not be operating appropriate procedures for supporting people with mental health problems. There is a need for local protocols to be implemented that include routine screening for mental health issues and liaison with mental health care providers.